Oxidative stress induced in microorganisms by zero-valent iron nanoparticles - Ševců, Alena; El-Temsah, Yehia S; Joner, Erik J; Černík, Miroslav (Microbes and environments, 2011)
Nanoscale zero-valent iron particles (nZVI), with sizes smaller than 100 nm, are promising for environmental remediation of polluted water, soil and sediments. nZVI particles have high potential for migration in the environment and are likely to interact not only with pollutant chemicals but also with living organisms. For these reasons, an environmental concern is rising with respect to unintended effects that need to be weighed against the benefits of remediation. The nZVI particles have a tendency to release electrons and Fe(2+). The Fe(2+) can convert less reactive hydrogen peroxide to more reactive oxygen species, particularly hydroxyl radicals, via the Fenton reaction. Hydroxyl radicals show strong biochemical activity and can react directly with membrane lipids, proteins and DNA. Reactive oxygen species are normally scavenged by antioxidants and various enzymes; however, elevated concentrations of ROS in microbial cells can result in oxidative stress. Cells under severe oxidative stress show various dysfunctions of membrane lipids, proteins and DNA. This review focuses on the processes resulting in oxidative stress and on up-to-date studies of nZVI-induced intracellular changes leading to such stress in microorganisms.
Keywords: železo; Stress, Physiological; Oxidative Stress; fyziologický stres; regenerace a remediace životního prostředí; Nanoparticles; Environmental Restoration and Remediation; oxidační stres; Bacteria; Iron; nanočástice